Sperm and seminal plasma RNAs: what roles do they play beyond fertilization?. Issue 4 (October 2019) - Jodar, Meritxell
Abstract : The paternal contribution to the new individual is not just limited to half the diploid genome. Recent findings have shown that sperm delivers to the oocyte several components, including a complex population of RNAs, which may influence early embryo development and the long-term phenotype of the offspring. Although the majority of sperm RNAs may only represent spermatogenic leftovers with no further function, the male gamete provides a specific set of RNAs to the oocyte that is able to modulate gene expression in the preimplantation embryo. Those sperm transcripts include coding and non-coding RNAs that might either be translated by the oocyte machinery or directly regulate embryo gene expression at the transcriptional or post-transcriptional level. Interestingly, some sperm RNAs seem to be acquired during post-testicular maturation through active communication between sperm and epididymal and seminal exosomes released by the epididymis and the male accessory sex glands, respectively. Exosomes contained in the seminal plasma seem to not only interact with the spermatozoa but also with cells from the female reproductive tract, modulating their gene expression and influencing female immune response triggered by the semen. This review also considers the findings that indicate the role of semen RNAs in preimplantation embryo development and offspring phenotypes. In this regard, different studies supporting the hypothesis of paternal epigenetic inheritance of altered metabolic phenotypes associated with environmental exposures are discussed. Lastly, potential mechanisms that could explain the impact of semen RNAs to both early embryogenesis and paternal epigenetic inheritance are suggested.